ANALISIS POTENSI INTEGRASI TEACHING FACTORY BERBASIS KEARIFAN LOKAL PADA SMK DI KOTA PALANGKA RAYA - Supriyadi Supriyadi; Ahmad Eko Suryanto; I Made Supatra; Steven Yulando; Toharudin Toharudin; Gabriel Alfran Valentino Juli (Steam Engineering, 2026)
Vocational education, particularly Vocational High Schools (SMKs), plays a strategic role in preparing competent human resources who are adaptable to labor market demands. One approach developed to enhance the relevance of vocational learning to industry needs is the Teaching Factory (TEFA) model. However, the implementation of TEFA in many vocational schools often faces challenges related to the market relevance of the products. This study aims to analyze the potential integration of local wisdom-based TEFA and to map its alignment with the spectrum of vocational competencies in SMKs in Palangka Raya City. This research employed a qualitative approach with an exploratory case study design. Data were collected through in-depth interviews, field observations, and document analysis involving 16 SMKs and local small and medium enterprises (SMEs) producing local wisdom-based products. Data were analyzed using the interactive model of Miles, Huberman, and Saldana. The findings indicate that Palangka Raya City possesses significant local wisdom-based economic potential in crafts, culinary products, herbal products, fashion, and tourism sectors. Furthermore, the vocational competencies available in the 16 SMKs demonstrate strong alignment with the development of local wisdom-based TEFA products. This integration has the potential to establish a collaborative TEFA ecosystem among SMKs across upstream and downstream sectors, thereby enhancing graduates' employability skills and supporting the growth of the regional creative economy.